2019
DOI: 10.3390/cells8030258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MSCs and MSC-Derived Extracellular Vesicles on Human Blood Coagulation

Abstract: Mesenchymal stem cells (MSCs) have emerged as a potent therapeutic tool for the treatment of a number of pathologies, including immune pathologies. However, unwelcome effects of MSCs on blood coagulation have been reported, motivating us to explore the thrombotic properties of human MSCs from the umbilical cord. We revealed strong procoagulant effects of MSCs on human blood and platelet-free plasma using rotational thromboelastometry and thrombodynamic tests. A similar potentiation of clotting was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 70 publications
5
106
0
2
Order By: Relevance
“…To correct the procoagulant effect of AF MSCs in this study, we found that more than double that (12 000 U) was required to normalize the TEG R time. However, a recent study by Silachev et al potentially calls into question the efficacy of heparin treatment to ameliorate the procoagulant effects of CCTs . In their study, blood from newborn infants at high risk of thrombosis was collected 0.5‐1 hour after systemic heparinization at a dose of 5 U/h/kg.…”
Section: Discussionmentioning
confidence: 99%
“…To correct the procoagulant effect of AF MSCs in this study, we found that more than double that (12 000 U) was required to normalize the TEG R time. However, a recent study by Silachev et al potentially calls into question the efficacy of heparin treatment to ameliorate the procoagulant effects of CCTs . In their study, blood from newborn infants at high risk of thrombosis was collected 0.5‐1 hour after systemic heparinization at a dose of 5 U/h/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that exosomes act as crucial mediators of intercellular communication (7)(8)(9). In addition, they function in numerous physiological processes, such as blood coagulation (10), tissue repair, skin regeneration (11) and immune modulation (12); therefore, exosomes play roles in cancer and other pathological processes such as in cancer, cerebral ischemia and obesity (13)(14)(15).…”
Section: Introductionmentioning
confidence: 97%
“…On the clinical side, little is known regarding optimal therapeutic doses and optimal route(s) of administration [89]. Regarding safety, MSC-EVs have been shown to exhibit procoagulant activity, similarly to their cells of origin [98], a property that could cause concern in patients prone to thrombotic events such as those with SARS-CoV-2 infection.…”
Section: The New Therapeutic Potential Of Extracellular Vesiclesmentioning
confidence: 99%